Myrsidea claytoni (Phthiraptera: Menoponidae) from Cymbirhynchus macrorhynchos (Passeriformes: Eurylaimidae): a case of natural host switching - Sychra, Oldrich; Najer, Tomas; Kounek, Filip; Hung, Nguyen Manh; Tolstenkov, Oleg O (The Journal of parasitology, 2014)
Thirty-two black-and-red broadbill Cymbirhynchus macrorhynchos were examined for chewing lice in Vietnam. All birds examined were parasitized by Myrsidea claytoni. Mean abundance was 27.3, with intensity range 5-80 lice per bird. This is the first report of a Myrsidea from this host, although the females differ slightly from the original description of M. claytoni from Pycnonotus eutilotus in the shape of metanotum and of tergites I-II. So this is also the first record of 1 species of Myrsidea from 2 very distantly related hosts. Although the original hosts of M. claytoni belong to the family Pycnonotidae, C. macrorhynchos is a member of the family Eurylaimidae, representing the Old World Suboscines, which are considered as a basal lineage among passerines. Therefore, our record represents an interesting case of natural host switching. The high prevalence as well as the intensity of infestation show that M. claytoni is well established on C. macrorhynchos in Vietnam.
Keywords: Animals; Passeriformes; prevalence; Bird Diseases; Female; zvířata; mužské pohlaví; nemoci ptáků; zavšivení; Male; Prevalence; Sex Ratio; poměr pohlaví; Amblycera; ženské pohlaví; Vietnam; Lice Infestations